2009
DOI: 10.1258/jms.2009.009012
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Interval Breast Cancer Rates in Norway and North Carolina: Results and Challenges

Abstract: Objective To compare interval breast cancer rates (ICR) between a biennial organized screening programme in Norway and annual opportunistic screening in North Carolina (NC) for different conceptualizations of interval cancer. Setting Two regions with different screening practices and performance. Methods 620,145 subsequent screens (1996–2002) performed in women aged 50–69 and 1280 interval cancers were analysed. Various definitions and quantification methods for interval cancers were compared. Results ICR for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 24 publications
3
21
0
1
Order By: Relevance
“…The findings were consistent with other international studies [2][3][4]. Different radiological reading procedures have been suggested as a possible reason for the findings [1,2,4].…”
supporting
confidence: 92%
“…The findings were consistent with other international studies [2][3][4]. Different radiological reading procedures have been suggested as a possible reason for the findings [1,2,4].…”
supporting
confidence: 92%
“…Previous studies based on CMR have reported higher proportions of screen detected cases (e.g. Henderson et al reported 80% of cases were screen detected using a 1 year-interval(14); Hofvind et al reported 60% of cases were screen detected given the 24-month definitions used herein(11)). We were unable to retrospectively review mammographic images to confirm which interval cases arose from false negatives, but we minimized misclassification within screen and interval-detected groups by classifying women with missing screening data as ‘unknown’.…”
Section: Discussionmentioning
confidence: 80%
“…These cancers tend to be higher stage and grade at the time of diagnosis whereas screen-detected cancers have been reported to have more indolent molecular characteristics(710). The proportion of interval cancers in screened populations varies from 14% to 38%(1114), depending on screening interval and underlying population breast cancer incidence rates(15). …”
Section: Introductionmentioning
confidence: 99%
“…Two qualitative studies of the experiences of women diagnosed with interval cancer indicate that some women postponed help-seeking when they developed breast cancer symptoms, due to the negative mammography examination [143] and that despite being diagnosed with interval cancer, the interviewed women remained positive towards the screening program [142]. …”
Section: Discussionmentioning
confidence: 99%
“…The study is based on the same qualitative methods and interviews as the study by Solbjør et al described above [143].…”
Section: Characterization Strengths and Limitationsmentioning
confidence: 99%